Microwave properties of HTS films: measurements in millimeter wave range: Experimental Methods and Applications - Cherpak, N.T.; Barannik, A.A.; Prokopenko, Yu.V.; Filipov, Yu.F.; Vitusevich, S.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
A theoretical and experimental justification of an approach proposed and developed by us for surface impedance standard measurements of HTS films is presented. An analysis of the electromagnetic properties of quasi-optical dielectric resonators with conducting endplates, which provides a theoretical background for studies of HTS films in the millimeter wave range, is performed. With this technique, the highest quality modes, namely whispering gallery modes, are excited in a dielectric cylindrical disc sandwiched between HTS films. Considerable enhancement of the sensitivity of surface resistance measurements in the millimeter wave range is demonstrated, which is important for the fundamental investigation of superconductor physics. It is also shown that the measured frequency shift in the resonator with the HTS endplates as a function of the temperature reveals a possibility for accurate evaluation of the field penetration depth in HTS films.